2011
DOI: 10.1186/1532-429x-13-17
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia delays the development of stone heart from untreated sustained ventricular fibrillation - a cardiovascular magnetic resonance study

Abstract: Background'Stone heart' resulting from ischemic contracture of the myocardium, precludes successful resuscitation from ventricular fibrillation (VF). We hypothesized that mild hypothermia might slow the progression to stone heart.MethodsFourteen swine (27 ± 1 kg) were randomized to normothermia (group I; n = 6) or hypothermia groups (group II; n = 8). Mild hypothermia (34 ± 2°C) was induced with ice packs prior to VF induction. The LV and right ventricular (RV) cross-sectional areas were followed by cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The loss of LV compliance after CME in the present study resembles the “stone heart” after untreated cardiac arrest, which results from ATP loss and subsequent cardiomyocyte contracture 19,20 . Cooling in isolated rat hearts (28 °C) 19 and pigs in vivo (33 °C) 21 delayed the onset of a stone heart, and a similar effect within the embolized LV territory and the hypoperfused but viable infarction border zones may underlie better preserved LV compliance during MH in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…The loss of LV compliance after CME in the present study resembles the “stone heart” after untreated cardiac arrest, which results from ATP loss and subsequent cardiomyocyte contracture 19,20 . Cooling in isolated rat hearts (28 °C) 19 and pigs in vivo (33 °C) 21 delayed the onset of a stone heart, and a similar effect within the embolized LV territory and the hypoperfused but viable infarction border zones may underlie better preserved LV compliance during MH in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…The benefit of mild therapeutic hypothermia on post resuscitation myocardial dysfunction has also been reported. We found that mild hypothermia has a profound effect in lengthening the time period of untreated ventricular fibrillation before "stone heart" or global ischemic contracture of the left ventricle develops (32). Another report showed that mild post resuscitation hypothermia ameliorates some of the myocardial dysfunction commonly seen post cardiac arrest (33).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, it appears that Drp1 inhibition is protective when initiated in the reperfusion stage of IR injury. Improving the lusitropic properties of the heart and counteracting the “stone heart” seen in clinical cardiac arrest (35, 36) could have significant clinical benefit. Its benefits may also extend to other ischemic heart conditions, including acute coronary syndromes and postcardiovascular bypass surgery.…”
Section: Discussionmentioning
confidence: 99%